'I Wanted to See the Man with that Mark on his Forehead': A historian, her childhood experiences, and the power of memory - Koivunen, Pia (Open book publishers, 2025)
This chapter discusses the use of one's own memory as a source in historical research. As a historian who has employed interviews, memoirs, travelogues, and diaries in my research, I now put my own memory to a test and examine how using my own memories differs from studying the memories of others. The chapter explores my memories of Mikhail Gorbachev's visit to Finland in 1989 and compares them with other sources, such as interviews with classmates, contemporary print media, photographs, and film material of the event. In a dual role of researcher and the researched, I demonstrate how lived experiences are supported by narrative elements and, in the end, how powerful memory can be.
(An)Archive: Childhood, Memory, and Cold War